A Study Of Hydrocyclone Classification Of Coal Fines By CFD Modeling And Laboratory Tests - S. Torno (Society for Mining, Metallurgy & Exploration, 2011)
The elimination of ultrafine (<10 µm) clay particles is essential to the treatment of abandoned coal-washing plant tailings for the recovery of the remaining coal fraction by enhanced gravity processing. Effective hydrocyclone classification is required to remove this fraction. The highly variable composition and particle size distribution of such wastes creates significant difficulties in the operation of hydrocyclones for such classifications. Hydrocyclone laboratory investigations and their plant setup require lengthy or time-consuming tests. The use of empirical models of such classifications frequently requires modification to correspond to actual operating conditions. Results of the evaluation of computational fluid dynamics (CFD) modeling to predict hydrocyclone classification of coal-washing plant tailings are presented. Results of the standard k-epsilon turbulence, SSG turbulence and large eddy simulation CFD models are compared with the results obtained from analyzed hydrocyclone classifications. The CFD models tested are shown to be very effective in the simulation of hydrocyclone classifications for the determination of the classification particle size and adequate for determining the efficiency index values for many applications. The large eddy simulation model was identified as the most precise, but it is recommended that all three models be improved simulations of classifications above and below the classification particle size.